2019
DOI: 10.1002/chem.201900108
|View full text |Cite
|
Sign up to set email alerts
|

Rare‐Earth‐Metal Pentadienyl Half‐Sandwich and Sandwich Tetramethylaluminates–Synthesis, Structure, Reactivity, and Performance in Isoprene Polymerization

Abstract: Targeting the synthesis of rare‐earth‐metal pentadienyl half‐sandwich tetramethylaluminate complexes, homoleptic [Ln(AlMe4)3] (Ln=Y, La, Ce, Pr, Nd, Lu) were treated with equimolar amounts of the potassium salts K(2,4‐dmp) (2,4‐dmp=2,4‐dimethylpentadienyl), K(2,4‐dipp) (2,4‐dipp=2,4‐diisopropylpentadienyl), and K(2,4‐dtbp) (2,4‐dtbp=2,4‐di‐tert‐butylpentadienyl). The reactions involving the larger rare‐earth‐metal centers lanthanum, cerium, praseodymium, and neodymium gave selectively the desired half‐sandwich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…This can be traced to either partial loss of coordinated solvents or the high air‐ and moisture‐sensitivity. Similar observations for other organometallic rare‐earth metal complexes have previously been described in the literature [6b, 14, 22, 26a, 34] . Furthermore, we provided some explanations in the experimental section below where necessary.…”
Section: Methodssupporting
confidence: 83%
“…This can be traced to either partial loss of coordinated solvents or the high air‐ and moisture‐sensitivity. Similar observations for other organometallic rare‐earth metal complexes have previously been described in the literature [6b, 14, 22, 26a, 34] . Furthermore, we provided some explanations in the experimental section below where necessary.…”
Section: Methodssupporting
confidence: 83%
“…Previous studies from our group investigating the rare-earth metal bis­(tetra­methyl­alum­inate) library revealed that half-sandwich complexes (L)­Ln­(AlMe 4 ) 2 (L = Cp R , Flu R , pentadienyl) ,, display the most efficient precatalysts for the polymerization of isoprene, in terms of activity and stereospecificity of the polymer. In order to assess the performance of indenyl complexes 1a – d , the respective binary catalyst systems were examined in IP polymerization (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the precatalysts 1a – d were activated with 1 equiv of cocatalyst [Ph 3 C]­[B­(C 6 F 5 ) 4 ] ( A ), [Ph­NHMe 2 ]­[B­(C 6 F 5 ) 4 ] ( B ), or B­(C 6 F 5 ) 3 ( C ). As previously shown, fluorenyl and pentadienyl half-sandwich complexes can undergo “ancillary” ligand abstraction when activated with cocatalyst A or B . , Therefore, it was crucial to examine whether indenyl half-sandwich complexes would behave like the fluorenyl congeners or display the desirable coordination stability of Cp* complexes. The 1 H NMR spectra of 1 with cocatalyst A in C 6 D 6 at ambient temperature indicated that the activation proceeds via methyl group abstraction and formation of 1,1,1-triphenylethane and noncoordinated trimethylaluminum (Scheme , Figure S37).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations